(3GdEaGOGJ aj TQM GdRjGOGJs - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s ((3HQgGf Hf SdjeGf GdSeQi s)
(3ChdgG (B:s
(3EaJJMJ TQM cJGH GdRjGOGJ hEjGg JYGdi GdJhajb ddEMbGb SCdJ hHGdYQhI GdhKbi ef ESJgOGFg hGYJUeJ hSHH Pdc Cf hbaJ Edi GdCFeI GdeNJdajf Edi GdeQJbjf s
(3BNQgG (B:s
(3cja hbO LYd GdCcd eG PcQ GSe Gddg Ydjg EeGQI GdEjLGH Hbhdg hcdhG eeG PcQ GSe Gddg Ydjg Ef cfJe HBjGJg eDefjf hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hgh TQM Ydi efJNH UOQ GdOjf SdjeGf ef TQM bGVi NGf Ydi GdRjGOGJ ddTjHGfi s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs